Multicultural education: Students’ voices - Maula Hidayatul Atqiya; Yazid Basthomi; Yusnita Febrianti (University of Muhammadiyah Malang, 2026)
Multicultural learning environments have become an increasingly salient feature of Indonesian higher education. However, how students make sense of cultural, linguistic, and academic differences within these settings remains underexplored, particularly from the perspective of those who move across regions. This study examines how postgraduate students interpret and negotiate multicultural academic life after transitioning from undergraduate institutions outside Java to an urban university context in Malang. Using qualitative design, the study involved 30 postgraduate students and generated data through focus group discussions and semi-structured interviews. The data were analyzed thematically, with particular attention to metaphor elicitation as an analytical resource. The findings indicate that students’ transitions involved multiple, interconnected adjustments. Participants described shifts in learning ethics characterized by heightened research expectations, stricter academic writing practices, and increased productivity demands. Cultural and linguistic differences, including variations in politeness norms, dialect use, and communication styles, initially generated uncertainty but were largely navigated through ongoing clarification and negotiation. Students also reported intercultural challenges related to academic norms, peer interaction, and everyday campus behaviour. At the same time, Malang’s urban academic ecology, marked by dense student activity, digital academic infrastructures, and a productivity-oriented learning culture, was widely perceived as enabling, fostering stronger discipline, motivation, and expanded academic horizons. Metaphors like lamp, rainbow and kue lapis show students view multicultural education as integrative, enriching process rather than conflict, highlighting need for culturally responsive support systems across academic linguistic socio-emotional